2015
DOI: 10.1128/aac.00345-15
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Markers and In Vitro Susceptibility to Doxycycline in Plasmodium falciparum Isolates from Thailand

Abstract: jDeterminations of doxycycline 50% inhibitory concentrations (IC 50 ) for 620 isolates from northwest Thailand were performed via the isotopic method, and the data were analyzed by the Bayesian method and distributed into two populations (mean IC 50 s of 13.15 M and 31.60 M). There was no significant difference between the group with low IC 50 s versus the group with high IC 50 s with regard to copy numbers of the Plasmodium falciparum tetQ (pftetQ) gene (P ‫؍‬ 0.11) or pfmdt gene (P ‫؍‬ 0.87) or the number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…A study in Kenya showed that 15 % of the isolates had an IC 50 >35 µM [ 83 ]. A recent study on 620 Thai isolates found a bimodal distribution [ 84 ]. The two groups identified presented with a mean value of 13.15 µM for the group of 591 isolates with low IC 50 and a mean value of 31.60 µM for the group of high IC 50 , including 29 isolates.…”
Section: Mechanism Of Resistance To Doxycyclinementioning
confidence: 99%
See 1 more Smart Citation
“…A study in Kenya showed that 15 % of the isolates had an IC 50 >35 µM [ 83 ]. A recent study on 620 Thai isolates found a bimodal distribution [ 84 ]. The two groups identified presented with a mean value of 13.15 µM for the group of 591 isolates with low IC 50 and a mean value of 31.60 µM for the group of high IC 50 , including 29 isolates.…”
Section: Mechanism Of Resistance To Doxycyclinementioning
confidence: 99%
“…A study of Senegalese isolates showed a lack of association between the number of copies of pfmdt and pftetQ and high IC 50 for doxycycline, essentially because of an insufficient number of isolates with high IC 50 [ 81 ]. There was an absence of association between the number of copies of pfmdt and pftetQ or the polymorphisms on pftetQ and susceptibility to doxycycline in P. falciparum isolates from Thailand and French Guiana [ 84 , 92 ]. Copy number of pfmdt and pftetQ and polymorphisms on pftetQ are not sufficient to explain reduced susceptibility to doxycycline, which may be multigenic.…”
Section: Mechanism Of Resistance To Doxycyclinementioning
confidence: 99%
“…A total of 89 African P. falciparum isolates, obtained at the French National Reference Centre for Imported Malaria, Hôpital Bichat, Paris, from patients hospitalized with malaria after having returned to France between January 2006 and December 2010, and 89 isolates obtained from the Shoklo Malaria Research Unit (Mae Sot, Thailand) from patients infected with P. falciparum from 2001 to 2010, were used. These isolates were previously tested to evaluate their pfmdt and pftetQ genes copy numbers [ 9 , 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, some recent publications have demonstrated that these molecular markers were certainly not only encountered in cases of reduced susceptibility to doxycycline [ 13 , 14 ] and were not associated with resistance in Thai isolates [ 14 ]. Therefore, it is necessary to investigate other hypotheses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation